The Hidradenitis Suppurativa Priority Setting Partnership. (1st December 2014) - Ingram, J.R.; Abbott, R.; Ghazavi, M.; Alexandroff, A.B.; McPhee, M.; Burton, T.; Clarke, T.
Summary: Background: Hidradenitis suppurativa (HS) has been neglected by medical researchers and society in general, despite being a relatively common, painful, chronic skin disease. Objectives: To generate a top 10 list of HS research priorities, from the perspectives of patients with HS, carers and clinicians, to take to funding bodies. Methods: A priority setting partnership was established between patients with HS, carers and clinicians, following the James Lind Alliance process. Survey 1 requested submission of HS uncertainties, which were grouped into 'indicative uncertainties' for prioritization in survey 2. The 30 highest‐ranked indicative uncertainties were reduced to a 'top 10' list using nominal group technique at a prioritization workshop attended by all relevant HS stakeholders. Results: In total 1495 potential uncertainties were submitted in survey 1, including 57% from patients with HS and carers, and grouped into 55 indicative uncertainties. Ranking in survey 2 was completed by 371 participants, 50% of whom were patients and carers. The final workshop was attended by 22 HS stakeholders and four facilitators and produced a top 10 list, the three highest priorities in descending order being (i) What is the most effective and safe group of oral treatments in treating HS? (ii) What is the best management of an acute flare? (iii)What is the impact of HS and its treatment on people with HS? Conclusions: The top 10 HS research priorities have been directly disseminated to funders to raise awareness of HS. The next step is to generate research questions that will provide the evidence needed to improve care for patients with HS.